P-409 The endometrial transcriptome of infertile women with and without recurrent implantation failure. (30th June 2022) - Bui, B; Van Hoogenhuijze, N; Olsen, C; Mackens, S; Kukushkina, V; Laisk, T; Meltsov, A; Altmäe, S; Salumets, A; Steba, G; Broekmans, F
Abstract: Study question: Does the endometrial transcriptome profile differ between infertile women with or without a recurrent implantation failure (RIF)? Summary answer: Although two different clusters emerged from the endometrial transcriptome data, these were not associated with clinical phenotype (RIF vs non-RIF). What is known already: Despite the transfer of morphologically 'good-quality' embryos in IVF/ICSI, implantation failure often occurs, which may be explained by impaired endometrial receptivity. In order to guide prognosis and use effective therapeutic interventions, identifying a gene expression profile predictive of endometrial receptivity as well as implantation failure, would be of great value. Additionally, transcriptome analysis may also shed light on alterations in biological processes responsible for the implantation failure. Thousands of potential biomarkers for endometrial receptivity have already been identified by transcriptomic approach, however due to differences in study methodology, there is little overlap of markers between studies. Study design, size, duration: Endometrial tissue was obtained from a cohort of 141 infertile women undergoing endometrial scratching within a randomised controlled trial (RCT) (SCRaTCH trial, NL5193/NTR5342). Briefly, women aged 18-44 years with failed implantation after one full IVF/ICSI cycle and planning a subsequent IVF/ICSI cycle, were eligible. Participants were followed-up until 12 months after randomisation, with the primary outcome being live birth, defined as the delivery of at least one live foetus after 24 weeks of gestation. Participants/materials, setting, methods: Endometrial tissue was obtained with an endometrial biopsy catheter in the midluteal phase of a natural cycle preceding subsequent IVF/ICSI. Biopsies were snap-frozen and stored at -80 °C until use. After thawing, total RNA isolation, library preparation and paired-end RNA-sequencing were performed. Raw data was preprocessed and mapped to GRCh38. Reads (counts per million) were normalised using library size. Differential gene expression (DGE) analysis was conducted using the EdgeR package with significance threshold FDR <0.05. Main results and the role of chance: Out of 141 endometrium samples, 107 were included in the RNA-sequencing based on RNA quality. For DGE analysis, data of two groups were compared: the 'fertile' group, women with a live birth after ≤3 good quality embryo(s) transfers (n = 23), and the RIF group, women with no live birth after ≥3 good quality embryo(s) transfers (n = 23). Two clusters were visible in the principle component analysis (PCA) plot showing transcriptome data of the fertile and RIF samples (cluster 1, n = 29; cluster 2, n = 10), which was not explained by clinical phenotype, as both clusters contained samples of both the fertile and RIF group. DGE analysis between the fertile and RIF group resulted in respectively 3 significantly upregulated and 0 significantly downregulated genes, whereas DGE analysis between the two clusters resulted in 2, 235 significantly upregulated and 2, 162 significantly downregulated genes. Enrichment analysis of differentially expressed genes between both clusters demonstrated upregulation of enriched terms mainly annotated to cell migration and downregulation of enriched terms mainly annotated to lipid and mitochondrial metabolism. Limitations, reasons for caution: A strength of the study is the large number of samples included. Bulk RNA-sequencing was conducted and there was a variation in LH-based timing of the biopsies (5-8 days after LH surge) for which adjustments of the transcriptome data for tissue cellular composition and menstrual cycle were performed. Wider implications of the findings: Future studies investigating underlying biological mechanisms in the endometrium in (in)fertility by a (multi-)omics analysis approach with standardised methodology are required to obtain consistencies in relevant biomarkers/pathways, and in due course create possibilities to improve and personalise care for infertile couples. Trial registration number: NL5193/NTR5342